Plastic products separator in building rubbish - WU HEZHI; WANG WENFEI (2017)
The utility model discloses a plastic products separator in building rubbish, including rubbing crusher, granule sieve separator and buoyancy sieving mechanism, the last material of installing of rubbing crusher adds the fill, just rubbing crusher's discharge gate passes through the feeding device and connects the granule sieve separator, the granule sieve separator is equipped with coarse grain discharge gate and thin granule discharge gate, the utility model discloses simple structure, convenient to use, recovery that wholly can effectual realization plastics, recovery efficiency is high. 本实用新型公开了种建筑垃圾中塑料制品分离装置，包括粉碎机、颗粒筛选机和浮力筛选装置，所述粉碎机上安装有物料添加斗，且所述粉碎机的出料口通过输料装置连接颗粒筛选机，所述颗粒筛选机设有粗颗粒出料口和细颗粒出料口，本实用新型结构简单，使用方便，整体可以有效的实现塑料的回收，回收效率高。